Is nephrology transfering to gerontonephrology? - Rutkowski, Bolesław (Przewodnik Lekarza/Guide for GPs, 2011)
During last quarter of age constant and significant ageing of human population is observed. According to the last prognosis in 2030 nearly 1/4 of people living in Poland and whole European Union will exceed 65 years. This fact is causing several social and medical problems which refers also to nephrology and nephrologists. It is important to remember that during advance in age several structural changes are developing in the kidneys leading to the decrease of glomerular filtration rate and disturbances of many tubular functions. These changes may cause the tendency to the development of very harmful complications like dehydration, hypo- or hypernatremia or metabolic acidosis. Also it has to be mentioned that these changes are causing significantly frequent appearance of chronic kidney disease in this group of people. Chronic kidney disease is observed in more than 30% of elderly persons. Simultaneously among patients with end stage renal disease needing renal replacement therapy significant increase of aged people is observed. It is worth to mention that in Poland among people starting dialysis therapy last years 54% and among patients on maintenance dialysis nearly 49% were people who accomplished 65 years. Also in the group of patients after renal transplantation still increase of the people in advanced age is observed. Data from Gdansk transplant unit are showing that ober 20% transplanted last year were people over 60 years old and totally on Poland this group gained 17.5%. All informations mentioned above leading to the conclusion that nephrology is becoming more and more gerontonephrology and this fact is obligating nephrologists to widen their knowledge and professional education taking into account geriatric problems.